2010
DOI: 10.1029/2009wr008900
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic characterization of the onset of and recovery from hypoxia in Tokyo Bay, Japan: Derived distribution analysis based on “strong wind” events

Abstract: [1] This paper uses derived distribution analysis to explore the process controls of the onset of and recovery from hypoxic conditions in Tokyo Bay, Japan. A conceptual, lumped model of dissolved oxygen (DO) dynamics in Tokyo Bay is proposed and, through comparison with a three-dimensional simulation model, is verified to have sufficient accuracy for the prediction of the onset of and recovery from hypoxia. This conceptual DO model was implemented in continuous simulation mode, with 14 years of wind data and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…Wind fields around Tokyo Bay were estimated using nine land‐based meteorological observation stations of the Automated Meteorological Data Acquisition System (AMeDAS System), since topography around the bay induces shear and curl in the wind field. Since the observed wind speed at a height of 10 m over Tokyo Bay has been found to be about twice that measured at a height of 10 m on land [ Nakayama et al ., ; Satoh et al ., ], we doubled the wind speeds observed by the AMeDAS system and then interpolated the wind vectors using an exponential weighting function. To validate this technique for estimating the wind fields, we compared the observed wind vectors at a station to the wind vectors interpolated without using the data from the station.…”
Section: Observationscontrasting
confidence: 61%
“…Wind fields around Tokyo Bay were estimated using nine land‐based meteorological observation stations of the Automated Meteorological Data Acquisition System (AMeDAS System), since topography around the bay induces shear and curl in the wind field. Since the observed wind speed at a height of 10 m over Tokyo Bay has been found to be about twice that measured at a height of 10 m on land [ Nakayama et al ., ; Satoh et al ., ], we doubled the wind speeds observed by the AMeDAS system and then interpolated the wind vectors using an exponential weighting function. To validate this technique for estimating the wind fields, we compared the observed wind vectors at a station to the wind vectors interpolated without using the data from the station.…”
Section: Observationscontrasting
confidence: 61%
“…(2012) and Nakayama et al . (), hypoxia tends to occur more often if the duration of strong wind events is less than 20 h. In other words, the future water quality of Tokyo Bay largely depends on wind climatology in a globally changing environment. However, it should be noted that the criteria for strong negative winds may change along with other meteorological and hydrological conditions around Tokyo Bay.…”
Section: Introductionmentioning
confidence: 97%
“…Positive winds were revealed to enhance exchange of sea water between the inner bay and the ocean, whereas negative winds tended to suppress exchange with the ocean and thus contribute to the onset of hypoxia. However, strong negative winds above a threshold of 10 m s −1 (‘strong wind’ events) were revealed to play the greatest role in rapid and strong recovery from hypoxia due to the mixing of the inner bay water with ocean water (Sato et al ., ; Nakayama et al ., ). Although such strong negative wind events are rare, their ecological impact may be disproportionately large in terms of determining the influence of hypoxia on aquatic organisms.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, climaterelated issues have been revealed to have significant implications for coastal and natural resource management (NOAA, 2006;Nakayama et al, 2010). Solomon et al (2007) and Dutta et al (2005) found that climate change increases the occurrence of natural disasters, such as storm surges or flood events, leading to environmental damage, which can in turn increase the impact of natural disasters (Belfiore, 2003;Hirabayashi and Kanae, 2009;Kwak et al, 2012;Ma et al, 2010;Walsh, 2004;Watson, 2008).…”
Section: Introductionmentioning
confidence: 99%